2003
DOI: 10.1046/j.1469-8137.2003.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Populus deltoides × Populus nigra (Populus × euramericana) clone I‐214 to high zinc concentrations

Abstract: Summary• We hypothesized that poplar can be useful for the extraction of zinc (Zn) from contaminated soils and water. However, the physiological response and the base of tolerance of poplar plants to this heavy metal are little known.• Plants of Populus deltoides × P . nigra ( P. × euramericana ) I-214 clone were grown in glasshouse and treated with three different Zn concentrations (1, 100 and 1000 µ M ). Growth analysis, Zn concentration in leaves, stem and roots, and photosynthetic parameters were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 37 publications
(44 reference statements)
7
66
1
Order By: Relevance
“…The internal leaf concentrations in this study are in the same order of magnitude, but slightly higher than those reported in hydroponically grown red maple, white pine and Norway spruce [8]. They are also higher than those observed in a study using the poplar variety I-214, which had leaf concentrations of 131 mg kg -1 of Zn after only two additions of 1000 µM solution [15].…”
Section: Discussioncontrasting
confidence: 53%
“…The internal leaf concentrations in this study are in the same order of magnitude, but slightly higher than those reported in hydroponically grown red maple, white pine and Norway spruce [8]. They are also higher than those observed in a study using the poplar variety I-214, which had leaf concentrations of 131 mg kg -1 of Zn after only two additions of 1000 µM solution [15].…”
Section: Discussioncontrasting
confidence: 53%
“…• C. Quantifications of Zn were determined after digestion in concentrated nitric acid (HNO3) by atomic absorption spectrophotometry (model 373; PerkinElmer, Norwalk, CT, USA), as previously described (Di Baccio et al 2003). Chemical analyses were validated by blanks and reference materials.…”
Section: Zinc Analysis In Rootsmentioning
confidence: 99%
“…"Indicators" have a relatively constant root uptake over a wide gradient of trace elements in the soil. Driven by the potential of their use to extract and remove (or stabilize) toxic metals from contaminated soils (Salt et al 1998), there has been recent progress in our understand ing of the uptake, translocation and compart mentation of heavy metals in poplars (e.g., Di Baccio et al 2003, Borghi et al 2007.…”
Section: Introductionmentioning
confidence: 99%